The fall and rise of Group A Streptococcus diseases - Barnett, T. C. (Epidemiol Infect, 2018)
Streptococcus pyogenes (or Group A Streptococcus, GAS) is a Gram-positive human pathogen responsible for a diverse array of superficial, invasive and immune-related diseases. GAS infections have historically been diseases of poverty and overcrowding, and remain a significant problem in the developing world and in disadvantaged populations within developed countries. With improved living conditions and access to antibiotics, the rates of GAS diseases in developed societies have gradually declined during the 20th century. However, genetic changes in circulating GAS strains and/or changes in host susceptibility to infection can lead to dramatic increases in the rates of specific diseases. No situations exemplify this more than the global upsurge of invasive GAS disease that originated in the 1980s and the regional increases in scarlet fever in north-east Asia and the UK. In each case, increased disease rates have been associated with the emergence of new GAS strains with increased disease-causing capability. Global surveillance for new GAS strains with increased virulence is important and determining why certain populations suddenly become susceptible to circulating strains remains a research priority. Here, we overview the changing epidemiology of GAS infections and the genetic alterations that accompany the emergence of GAS strains with increased capacity to cause disease.